Cartographies of Madrid : Contesting Urban Space at the Crossroads of the Global South and Global North - Geist, Anthony L., 1945-; Bermúdez, Silvia (Hispanic issues (Vanderbilt University), 2019)
"This volume maps out the different configurations of Madrid as crossroads of the Global South and Global North by investigating the ways in which capital--political, cultural and economic--has been both exalted and challenged in Madrid, the capital city of Spain, from the decades preceding the end of the Franco dictatorship (1939-1975) to the present. In tracing the intersections drawn and redrawn by capital in the capital city of Spain Cartographies of Madrid assesses how the Global South and the Global North coexist in the same geographic space, and the ways in which this cohabitation has resulted in a challenge to urban exclusion and the notion of "politics as usual." The book brings together essays by acclaimed scholars from the US and Spain. Ideal for anyone with interest in urban studies, global studies, and Spanish Cultural Studies"--